Manajemen Asuhan Kebidanan pada NY.S Masa Nifas Fisiologis 3 Hari Post Partum di PMB BD. Riyanti, STR.KEB Bangetayu Kulon Genuk Kota Semarang Provinsi Jawa Tengah Tahun 2024 - Irma Suryani; Febriana Sari; Riyanti Riyanti; Sonia Novita Sari; Juliana Munthe (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
postpartum period is the period a woman goes through, starting after giving birth to the products of conception (baby and placenta) and ending up to 6 weeks after giving birth. During the postpartum period, the reproductive organs will slowly experience changes to the state before pregnancy. This change in the reproductive organs is called involution. Postpartum care is needed during this period because it is a critical period for both mother and baby. It is estimated that 60% of maternal deaths due to pregnancy occur after delivery and 50% of postpartum deaths occur within the first 24 hours. Postpartum care is carried out to reduce maternal mortality because the postpartum period is a critical period that needs monitoring. Results: care for NY "S" with post partum physiology 3 days ago with complaints that the stomach still felt bloated and little milk came out and during these 3 days no potential problems were found such as signs of mastitis, blocked breast milk, breast abscess, and breast cancer . However, the breast milk comes out a little because there is no stimulation by the way the baby breastfeeds on the mother, the uterine contractions are good and the lochia is appropriate. Conclusion: From the case study after examining and analyzing data on mothers and mothers 3 days postpartum at PMB NY Bd. Riyanti in 2024, the postpartum period is proceeding normally, vital signs are within normal limits and documentation and actions have been carried out on NY "S" with the result that no gaps were found between the theory and the cases obtained.